Indigenous children from three countries with non‐cystic fibrosis chronic suppurative lung disease/bronchiectasis. Issue 2 (8th February 2013) - Singleton, Rosalyn J.; Valery, Patricia C.; Morris, Peter; Byrnes, Catherine A.; Grimwood, Keith; Redding, Gregory; Torzillo, Paul J.; McCallum, Gabrielle; Chikoyak, Lori; Mobberly, Charmaine; Holman, Robert C.; Chang, Anne B.
Summary Objective Indigenous children in developed countries are at increased risk of chronic suppurative lung disease (CSLD), including bronchiectasis. We evaluated sociodemographic and medical factors in indigenous children with CSLD/bronchiectasis from Australia, United States (US), and New Zealand (NZ). Methods Indigenous children aged 0.5–8 years with CSLD/bronchiectasis were enrolled from specialist clinics in Australia (n = 97), Alaska (n = 41), and NZ (n = 42) during 2004–2009, and followed for 1–5 years. Research staff administered standardized parent interviews, reviewed medical histories and performed physical examinations at enrollment. Results Study children in all three countries had poor housing and sociodemographic circumstances at enrollment. Except for increased household crowding, most poverty indices in study participants were similar to those reported for their respective local indigenous populations. However, compared to their local indigenous populations, study children were more often born prematurely and had both an increased frequency and earlier onset of acute lower respiratory infections (ALRIs). Most (95%) study participants had prior ALRI hospitalizations and 77% reported a chronic cough in the past year. Significant differences (wheeze, ear disease and plumbed water) between countries were present. Discussion Indigenous children with CSLD/bronchiectasis from three developed countries experience significant disparities in poverty indices in common with their respective indigenous population; however, household crowding, prematurity and early ALRIs were more common in study children than their local indigenous population. Addressing equity, especially by preventing prematurity and ALRIs, should reduce risk of CSLD/bronchiectasis in indigenous children. Pediatr Pulmonol. 2014; 49:189–200. © 2013 Wiley Periodicals, Inc.